Electronic and magnetic properties of defected MoS2 monolayer - Hari Krishna Neupane; Narayan Prasad Adhikari (Bibechana, 2021)
It is interesting to understand the effect of defects in 2D materials because vacancy defects in 2D materials have novel electronic and magnetic properties. In this work, we studied electronic and magnetic properties of 1S vacancy defect (1Sv-MoS2), 2S vacancy defects (2Sv-MoS2), 1Mo vacancy defect (Mov-MoS2), and (1Mo & 1S) vacancy defects ((Mo-S)v-MoS2) in 2D MoS2 material by first-principles calculations within spin-polarized density functional theory (DFT) method. To understand the electronic properties of materials, we have analyzed band structures and DOS calculations and found that 1Sv-MoS2 & 2Sv-MoS2 materials have semiconducting nature. This is because, 1Sv-MoS2 & 2Sv-MoS2 materials open a small energy band gap of values 0.68 eV & 0.54 eV respectively in band structures. But, in Mov-MoS2 & (Mo-S)v-MoS2 materials, energy bands around the Fermi level mix with the orbital’s of Mo and S atoms. As a result, bands are split and raised around and above the Fermi energy level. Therefore, Mov-MoS2 & (Mo-S)v-MoS2 materials have metallic nature. We found that MoS2, 1Sv-MoS2 & 2Sv-MoS2 materials have non-magnetic properties, and Mov-MoS2 & (Mo-S)v-MoS2 materials have magnetic properties because magnetic moment of MoS2, 1Sv-MoS2 & 2Sv-MoS2 materials have 0.00 µB/cell value and Mov-MoS2 & (Mo-S)v-MoS2 materials have 2.72 µB/cell & 0.99 µB/cell  respectively. Therefore, non-magnetic MoS2 changes to magnetic Mov-MoS2 & (Mo-S)v-MoS2 materials due to Mo and (1Mo & 1S) vacancy defects.  The magnetic moment obtained in Mov-MoS2 & (Mo-S)v-MoS2 materials due to the distribution of up and down spins in 4p, 4d & 5s orbitals of  Mo atoms and 3s & 3p orbitals of S atoms in structures. The significant values of the magnetic moment are given by distributed spins in 4d orbital of Mo atoms and 3p orbital of S atoms.